Impact of Industrial Pollutants on the Well-being of Residents in Obajana Cement Factory Area, Kogi State, Nigeria - Dare Abubakar Baba; Babatunde Ekundayo; Samson Adebayo Babatunde; Rasheed Onigbegi Ambali; Abdulkareem Hussein Bibire; Kamalud-Deen Adekunle Uthman (Pan-African Journal of Health and Environmental Science, 2025)
Background: While industrial construction supports societal growth, the Obajana cement factory in Ajaokuta, Kogi State, Nigeria, has caused significant environmental issues due to toxin release. This study assessed the impact of industrial pollution on the physical and mental well-being of people living near the Obajana cement industry.